HOW GUANXI INFLUENCES THE TURNOVER INTENTIONS, AND JOB SATISFACTION OF PRIVATE SECTOR EMPLOYEES FROM SAUDI ARABIA - Alwaheeb, Mohammed Abdulwahab; Jianqiao, Liao (European Scientific Journal, ESJ, 2015)
Saudi Arabia has one the most diversified and rapidly changing job markets among the Arab countries. One the most felt changes include the increase in the use of guanxi in the private sector, either between businesses or individuals. The use of guanxi enables individuals to acquire favors from other persons, which places the beneficiary in a better position, especially on competitiveness. Guanxi can have various effects on the recipient as well as the other members of the organization; some of the most affected values include the turnover intention and job satisfaction. However, the impact of the guanxi effect on job satisfaction and the turnover intention may be dependent on over variables like the job security and situational factors such as individual performance and organizational justice. The proposed study aims at explaining the effect of the guanxi concept in the turnover intention and job satisfaction in the Saudi Arabian private sector. The study will consider the contribution of job security, individual performance, and organizational justice in the development of the relationship